Информационный метод моделирования непрерывных нечетких измерений квантового состояния в эксперименте по наблюдению раби-осцилляций - Мельник, С. И.; Слипченко, Н. И.; Мельник, С. С. (ХНУРЭ, 2010)
The dynamics of two-level quantum system in a mode of Rabi-oscillations in continuous fuzzy supervision. This interaction is described by the information method. Quantum Bayes theorem and scale invariance is used in the transition to a continuous description. . This makes it possible to do without specifying the mechanism of interaction between the observed system and the sensor. Write the equation of Chapman-Kolmogorov and Fokker-Planck equation for this process. The possibility of comparing their solutions with experimental results. В последнее время большое внимание в физике уделяется как проблемам построения квантового компьютера, так и общетеоретическим аспектам описания физических процессов, обеспечивающих получение, передачу и преобразование квантовой информации.
Keywords: квантовый компьютер; квантовая информация; теория квантовых измерений; твердотельный кубит